Local Technical Agroclimatic Committees (MTAs) in Colombia - Blundo Canto, Genowefa; Moreno, Manuel; Ngaiwi, Mary; Gonzalez, Carolina (2025)
The Local Technical Agroclimatic Committees (MTAs) in Colombia are collaborative platforms that bring together farmers, scientists, government officials, and other stakeholders to co-produce and disseminate localized climate information for agricultural planning. Originating in 2013 and officially launched in Colombia in 2014, MTAs aim to strengthen climate resilience by translating forecasts into actionable guidance through monthly agroclimatic bulletins. This outcome evaluation focuses on five MTAs that demonstrated notable changes in practices, behaviors, and interactions. Using complexity-aware methods such as Outcome Harvesting and Outcome Evidencing, the evaluation identified 13 outcomes, of which 5 were deeply validated through stakeholder interviews. Key results include behavioral changes in planning and preparedness, improved collaboration across sectors, and increased climate literacy. Despite demonstrated impact, the MTAs face challenges such as limited inclusion of marginalized groups, weak adoption monitoring, and dependency on short-term agreements. Recommendations include institutionalizing MTAs, enhancing inclusivity, improving M&E systems, and strengthening local ownership and digital communication strategies. The findings affirm the MTAs' contribution to adaptive agricultural decision-making and provide insights for their sustained impact and scalability.